FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KUALITAS AUDIT (Studi Empiris pada Pemeriksa BPK Perwakilan Provinsi Jawa Tengah) - Sinta Mahardika, 16.05.62.0008; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2018)
This research entitled “Factors Influenced Toward Audit Quality (Empirical Study on Auditors of BPK Representative Office of Central Java Province)”, purposed to analyze the influence of independency, integrity, profesionalism, competency, job experience, ethic compliance, and time budget pressure to audit quality on the auditors of BPK Representative Office of Central Java Province. The population of this study were 126 auditors. Sampling was conducted using a purposive sampling method and number of samples were 99 respondents. Primary data collection method used in this study, and analyzed by multiple regression model. The result showed that independency, integrity, profesionalism, competency,and job experience have a positive and insignificant influence to audit quality. Meanwhile job experience has a positive and insignificant influence to audit quality, and time budget pressure has a negative and insignificant influence to audit quality.Keywords: independency, integrity, profesionalism, competency, job experience, ethic compliance, time budget pressure, audit quality